A Dissident Archive of Climate Change Fiction: Feminist Afrofuturist Literary Voices on the Anthropocene (Altre Modernità, 2024)
Drawing from Shelley Streeby’s definition of “visionary fiction” to describe Indigenous and people of colour futurisms as fiction that “extends beyond cli-fi in its rich and deep connections to social movements and everyday struggles” (Streeby 4-5) and that attempts to decolonise the imagination of climate change, this article will propose an analysis of feminist Afrofuturist climate change fiction. The absence of climate justice from several novels that are considered to be part of the emerging canon of climate fiction, and their one-dimensional representation of gender, race, and the other-than-human (Schneider-Mayerson; Gaard), require alternative ways of responding to the climate change crisis. My analyses seek to demonstrate that feminist Afrofuturist representations of the Anthropocene not only treat climate justice as a central issue, but they also make an insightful critical intervention capable of imagining a rupture from master—and mainstream—narratives of linear progress. This article, in particular, will propose an overview of some contemporary feminist Afrofuturist writers and filmmakers, such as Wanuri Kahiu, Nnedi Okorafor, and N. K. Jemisin.